The Effect of Nitrogen-Doped ATO Nanotubes on Radical Multiplication of Buffer Media by Visible Light Photocatalysis Rather UV. (29th September 2012) - Hu, Kan-Hung; Wang, Shing-Hoa; Hsu, Todd; Chen, Chien-Chon; Lin, Tai-Yuan; Tsai, Huei-Ting; Chiang, Hsiang-Ho
Abstract : The use of TiO2 in photodynamic therapy for the treatment of cancer has generally been studied in cultured cancer cells in serum-containing RPMI 1640 medium under visible light application rather than ultraviolet (UV) light. An ordered channel array of N-doped anodic titanium dioxide (ATO) has been successfully made for visible light application. ATO nanotubes in the anatase form with a length of 10 μ m are more effective than nanotubes of 1.8  μ m in length as a photocatalyst for radical multiplication in buffer solution by generating hydroxyl radicals and superoxide radical anions under UV-A exposure. Only the N-doped ATO is applicable to visible light photocatalysis for radical multiplication in RPMI 1640 + 1 % FBS and acrylamide, a free radical carrier.